The association between serum lipid profile and the prostate cancer risk and aggressiveness - Suh, Jungyo; Shin, Teak Jun; You, Dalsan; Jeong, In Gab; Hong, Jun Hyuk; Kim, Choung-Soo; Ahn, Hanjong (Frontiers in Oncology, 2023)
Purpose This study aims to evaluate the association of serum lipid profile on prostate cancer (PC) risk and aggressiveness. Methods Men who underwent prostate biopsy between January 2005 and December 2015 were retrospectively analyzed. The association between lipid profile and the risk, stage, and Gleason grade group (GG) of the PC were investigated. Sensitivity analysis was conducted using univariate and multivariate quantile analysis for lipide profile on the risk and stage of PC. Results Of the 1740 study populations, 720 men (41.4%) were diagnosed as PC. From multivariate logistic regression analysis, age, prostate specific antigen, triglyceride (odds ratio (OR):1.05, confidence interval (CI):1.03-1.07, p-value<0.001) significantly increased PC risk, while total cholesterol (OR:0.96, CI:0.92-0.99, p-value=0.011) significantly decreased the PC risk. The increase of serum triglyceride increased the risk of both of locally advanced (OR:1.03, CI:1.00-1.07, p-value=0.025) and metastatic PC (OR:1.14, CI:1.04-1.25, p-value=0.004). The increase of serum triglyceride increased the risk of GG2-3 (OR:1.03, CI:1.00-1.06, p-value=0.027) and GG4-5 (OR:1.04, CI:1.01-1.08, p-value=0.027). Univariate quartile analysis founded serum triglyceride increasing risk of locally advanced disease than organ confined disease. (OR: 1.00, 1.25, 2.04, 4.57 for 1st, 2nd, 3rd and 4th quartile, p-value<0.001). Adjusted multivariate quartile analysis confirmed statistically significant increasing PC risk of triglyceride (OR: 1.00, 1.25, 2.04, 4.57 for 1st, 2nd, 3rd and 4th quartile, p-value<0.001). Conclusions This study findings suggested increased in triglyceride level increased the risk PC. Increased in triglyceride level also associated with aggressive presentation of PC, with higher stage and GG.